Transforming forest education to meet the changing demands for professionals - Ratnasingam, Jegatheswaran; Ioras, Florin; Ab Latib, Hazirah; Mohamed, Shukri; Senin, Abdul Latib (Forest Research Institute Malaysia, 2018)
The traditional forestry practice is under increasing pressure to transform, driven primarily by a shifting public perception of sustainability, and developments in science, communications, and global markets. In this context, the existing forestry education model is poorly equipped to cope with changes sweeping through the forestry sector that are linked to digitisation and rapid development in the information technology sectors. In preparing professionals for forestry practice today, notable discrepancies between what potential employers want and what the forestry institutions provide are apparent. In response, when hiring graduates of professional forestry programmes, forestry employers have changed the skill set and competencies sought. A similar scenario is also observed in South-East Asia, which despite its abundant forest resources and robust forest industries, is also experiencing dwindling interest among young people and falling enrollment rates in its forestry education institutes. Prevailing financial constraints and political pressures on higher education make it difficult for educators to close the gap between forestry education and forest practice. Nevertheless, a concerted effort from all stakeholders in revising the existing forestry education model to incorporate new courses and skills that will better prepare future foresters, appears to be the way forward.